Library Revitalization as An Effort to Improve Students Literacy Ability at SDN 1 Kertaharja - Dierayani, Allysa Putri; Nur Elfaz, Zam Zam; Shofiatun Nisa, Wafa; Nurohmah Dona, Tiara Gita; Nita, Sri; Fitriyani, Seni D; Risma, Neng; Pratama, Muhamad Risky; Saparudin, Miftahul Rizki; Amelisqi, Lusi Bilqis; Sajidah, Febi Zulfa; Madani, Fathi Makia; Nurjaman, Diman; Pratiwi, Denisa Lestari; Nuraeni, Neni (LPPM Universitas Muhammadiyah Tasikmalaya, 2025)
Skills that must be possessed in the 21st century are literacy skills, namely the ability to receive information in reading and writing. Literacy through the library is one of the efforts to improve the literacy skills of students. The renovation of the library which is located at SDN 1 Kertaharja, Parakan Hamlet, Cimerak District, Pangandaran Regency. The initial condition of the library is to store goods such as sports equipment, school administration and school files, so that the benefits of the library as a place to read or borrow books for students are not optimal even though students' reading interest is high. The purpose of this revitalization activity is to restore the functioning of the library and improve the literacy skills of students, by decorating, rearranging books according to type so that they become an attractive place for students to read, borrow books or do assignments. The results after the activity showed that the enthusiasm of students to visit and start doing reading activities, doing assignments and every day the library was crowded. It is recommended for the school to maintain and improve the use of the library and appoint a better library manager